Corticosteroids and bone mass in asthma: comparisons with rheumatoid arthritis and polymyalgia rheumatica. Issue 6560 (6th December 1986) - Reid, D M; Nicoll, J J; Smith, M A; Higgins, B; Tothill, P; Nuki, G
Abstract : Bone mass has previously been shown to be reduced at peripheral bone sites in patients with bronchial asthma receiving corticosteroids. To assess whether total bone mass is reduced in asthma total body calcium was measured by in vivo neutron activation analysis in patients receiving various treatments for asthma and compared with results from normal controls and patients with rheumatoid arthritis and polymyalgia rheumatica. Compared with controls total body calcium was reduced by 13.6% (p less than 0.001) in patients with asthma receiving daily oral corticosteroids but by only 9.0% (p less than 0.005) in a similar group of patients who had received oral calcium supplements at the start of their corticosteroid treatment. Total body calcium was also reduced in a group of patients receiving only inhaled corticosteroids (8.8%; p less than 0.001) but not significantly reduced in a small group of patients with asthma who had never received these drugs. When compared with controls a group of patients matched for age and for dose of corticosteroids given for rheumatoid arthritis had a similar reduction in total body calcium to the patients with asthma receiving daily oral treatment (17.7%; p less than 0.001), but no such reduction was shown in patients with polymyalgia rheumatica. These findings suggest that the risk of bone loss with low dose oral corticosteroids in similar in asthma and rheumatoid arthritis. Further work is required to assess the clinical relevance of small losses of bone associated with the use of inhaled corticosteroids.